2015
DOI: 10.1542/peds.2015-1807
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Dravet Syndrome in a US Population

Abstract: OBJECTIVE: De novo mutations of the gene sodium channel 1α (SCN1A) are the major cause of Dravet syndrome, an infantile epileptic encephalopathy. US incidence of DS has been estimated at 1 in 40 000, but no US epidemiologic studies have been performed since the advent of genetic testing. METHODS: In a retrospective, population-based cohort of all infants born at Kaiser Permanente Northern California during 2007–2010, we elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(162 citation statements)
references
References 37 publications
(18 reference statements)
4
150
2
2
Order By: Relevance
“…Our estimate of the minimum incidence of DS in Japan, 1:45,800, is similar to the estimate of Brunklaus et al 7 for a United Kingdom cohort (1:40,900), and lower than estimates based on much smaller cohorts from the United States (1:20,900) and Denmark (1:22,000). 4,6 The estimates from United Kingdom and Japan are likely to be lower bounds because they are based entirely on the incidence of DS in patients reporting to a single clinic in each country. The proportion of individuals with truncation variants in our DS cohort is 55% (158/285).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our estimate of the minimum incidence of DS in Japan, 1:45,800, is similar to the estimate of Brunklaus et al 7 for a United Kingdom cohort (1:40,900), and lower than estimates based on much smaller cohorts from the United States (1:20,900) and Denmark (1:22,000). 4,6 The estimates from United Kingdom and Japan are likely to be lower bounds because they are based entirely on the incidence of DS in patients reporting to a single clinic in each country. The proportion of individuals with truncation variants in our DS cohort is 55% (158/285).…”
Section: Discussionmentioning
confidence: 99%
“…These multiple seizure types, which also tend to be refractory to treatment with antiepileptic drugs (AEDs), are associated with the onset of significant delays in cognitive, behavioral, and motor areas. DS is a rare disorder (OMIM: 607208) with an estimated incidence of 1:16,000–1:40,000 births . Approximately three fourths of patients with DS are found to have a variant in the voltage‐gated sodium channel gene, SCN1A .…”
mentioning
confidence: 99%
“…Large numbers of the parents of the patients with DS also indicated significant difficulties, including scoring in the abnormal range of the Strength and Difficulties Questionnaire (SDQ) for "conduct problems" (35%), "hyperactivity/ inattention" (66%), and problems in "peer relationships" (76%). Epilepsy/seizure severity, presence of myoclonic seizures, and age at onset of seizures were among the strongest independent predictors of poor HRQOL, further underscoring the urgency and need for more effective antiepileptic treatment options for this patient population [3]. Other studies have found that DS is associated with significant financial costs to the family and to society [8,12], significant behavioral and medical comorbidities (such as autism spectrum characteristics, communication impairments, cardiovascular conditions, dysautonomia, cognitive dysfunction, disturbed sleep, and motor impairment, among many others) [4,8,10,13], and negative impact on the quality of life of caregivers [4,8].…”
Section: Introductionmentioning
confidence: 96%
“…DS is relatively rare, with early estimates of the incidence ranging from 1 in 20,000 to 1 in 40,000 [2]; however, more recent research suggests it may affect one out of every 15,700 live births in the US [3]. Although children with DS usually evidence normal early development in the first few months of life, they soon develop prolonged febrile and afebrile generalized clonic or hemiclonic seizures [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dravet syndrome, previously known as severe myoclonic epilepsy in infancy, is a severe form of epilepsy that was first described by Charlotte Dravet in 1978 . Dravet syndrome has an incidence between 1 in 15 700 and 1 in 40 000 and is in 80 per cent of the patients associated with genetic abnormalities, mostly concerning a de novo mutation in the sodium voltage‐gated channel alpha subunit 1 gene ( SCN1A ) …”
mentioning
confidence: 99%